The Comparison of Chromosome Analysis Result by Manual and Software Cytovision Image Analysis Using Simple G-Banding - Gatot Ciptadi; Muhammad Nur Ihsan; Sri Rahayu; Veronica Margareta Ani Nurgiartiningsih; Mudawamah Mudawamah; Ardyah Ramadhina Irsanti Putri (Research Journal of Life Science, 2017)
Chromosome analysis or karyotyping is one among powerful methods to characterize normal or abnormal genetic of animals. On the basis of the important chromosome abnormalities and their negative effect in the near future, chromosomal investigation of breeding bull especially for Artificial Insemination (AI) began in different countries. Chromosomal abnormalities are usually considered to be a plague and are to eliminate. In Indonesia, AI implementation in cattle have been started intensively, especially using imported bulls (bos Taurus) i.e. Limousine. A number of cattle breeds have been reported on of the 50 exotic breeds with the problem of 1/29 translocation, then the chromosome analysis to be important to execute. Method performed by collecting blood samples from first generation of crossing breed Madura Cattle vs. Bos Taurus. Sample was added to medium (Karyo MAX Gibco) then placed in CO2 incubator at 38°C. Colcichine was added after 70 hours and kept for 2–3 hours. Slides were prepared and dried then stained with Giemsa. Slides were examined under high phase-contrast microscope, chromosome analysis using cytovision software and manual analysis straightly captured under microscope then arranged. Result of both method of karyotyping may accepted for analysing method of abnormal/normal chromosome. It showed that the 2 N diploid number of chromosome was normal was 60, there were 58 autosomes and 2 sex chromosomes in all cattle observed. It was observed that all cattle tested in this research were normal categories.  The karyotype analysis of all cattle showed that the chromosomes of one cell and different individual each breed varied in size, shape and position of centromere. It was recommended to performed chromosomal investigation of breeding bulls using advanced sophisticated tools of analysis like cytovision image analysis of fluorescent technique. Manual method was recommended only for analysis of normal or abnormal number of chromosome.